Edukasi Metode Kontrasepsi untuk Meningkatkan Pengetahuan Pasangan Usia Subur (PUS) di Wilayah Kerja Puskesmas Benteng Jampea - Ayu Rahayu Lestari (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The lack of knowledge of fertile couples (PUS) regarding various contraceptive methods remains a barrier to selecting the right contraceptive method, particularly the Long-Term Contraceptive Method (MKJP). This community service activity aims to increase the knowledge of fertile couples (PUS) regarding various contraceptive methods through health education. The activity was carried out on June 20, 2026, at the Village Office within the working area of ​​the Benteng Jampea Community Health Center, Selayar Islands Regency, involving 20 fertile couples. The methods used included interactive lectures, discussions, questions and answers, and the use of educational media in the form of flipcharts. Evaluation was carried out through pre-tests and post-tests using a question and answer method. The results of the activity showed an increase in knowledge in all aspects evaluated. Understanding of contraception increased from 55% to 100%, the purpose of contraception increased from 50% to 95%, the types of contraceptive methods increased from 45% to 95%, the advantages and disadvantages of contraceptive methods increased from 35% to 90%, knowledge of the Long-Term Pregnancy Period (MTMJ) increased from 30% to 90%, and the selection of contraception based on health conditions increased from 40% to 95%. The enthusiasm of participants during the activity also demonstrated the high public demand for reproductive health information. This activity demonstrated that health education through interactive counseling effectively increases the knowledge of reproductive-age couples about contraceptive methods, thus supporting informed decision-making in choosing a contraceptive method based on their health conditions and family needs.